Inhaler personalisation based on peak inspiratory flow (PIF) among dry powder inhaler users: a pilot randomised control trial (RCT) in COPD - Mas Fazlin Mohamad Jailaini; Jaya Muneswarao; Ching Zhen Hao; Rabia Hussain; Mohamed Faisal Abdul Hamid (Taylor & Francis Group, 2024)
Background: Dry powder inhalers (DPIs) are commonly used among patients with Chronic Obstructive Pulmonary Disease (COPD). These inhalers are breath-actuated, and require patients to generate sufficient peak inspiratory flow (PIF) to disaggregate the drug powder into respirable fine particles and deliver it to the lower airway tracts. Inhaler personalisation based on PIF among DPI users has not been studied in Malaysia, thus we conducted the present pilot study to determine the feasibility of conducting such research among COPD patients.Methods: This was an open-label pilot randomised control trial, conducted from June 2021-January 2022 at the respiratory clinic of Hospital Canselor Tuanku Muhriz, Universiti Kebangsaan Malaysia. Measurement of PIF was performed with In-Check DIAL G16 among adult COPD patients treated with DPI and had suboptimal PIF. Eligible subjects were randomised using block randomisation into two groups, either the interventional group or the control group.Results: Twenty-two COPD patients fulfilled the study criteria and were randomised to intervention (n = 11) and control (n = 11) groups. For the interventional group, there were statistically significant improvements between baseline and at 12 weeks for both FEV1 and CAT scores. The mean (% predicted) FEV1 were 54.6 ± 20.4% and 56.6 ± 19.8% (p = 0.026), pre-and post-intervention. The mean CAT score at baseline was 24.4 ± 5.8 and reduced to 19.6 ± 4.4 at 12 weeks (p = 0.012). For the control group, the mean (% predicted) FEV1 at baseline was 58.0 ± 21.9% and 56.5 ± 20.7% at 12 weeks, with no statistical significance difference (p = 0.143). However, there was a statistically significant difference in CAT scores at baseline and 12 weeks, with a mean of 26.5 ± 6.1 and 23.3 ± 5.6, respectively (p = 0.010).Conclusion: The findings from the present pilot RCT highlighted that inhaler personalisation based on PIF among COPD patients was feasible and practical.